2022
DOI: 10.15406/jabb.2022.09.00277
|View full text |Cite
|
Sign up to set email alerts
|

A review about Pastinaca sativa L. ssp. sylvestris [Mill.] secondary metabolite diversity and inducibility

Abstract: Pastinaca sativa L. ssp. sylvestris [Mill.] is a biennial, vegetable plant, whose root is tuberous and pivoting and the stem is tall and branched. The leaves are feather-sectate and the flowers are yellow, umbrella-shaped, compound. The fruits are dicariopse with winged edges. The plant is used in food and as a natural remedy in folk medicine. P. sativa is considered a very nutritious plant, important also due to its medicinal effects. The sweet taste and pleasant aroma made this vegetable indispensable in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated the pharmacological effects of P. sativa on various bodily systems, including the central nervous, respiratory, gastrointestinal, hepatic, skin, cardiovascular, and genitourinary systems [252], as well as its potential in mitigating stroke, atherosclerosis, and other coronary heart diseases. Additionally, P. sativa has been shown to have positive effects on cholecystitis, constipation, anorexia, stomach pain, bladder atony, spastic enterocolitis, mild insomnia, nephritis, dysuria, renal colic, endocrine disorders such as menstrual syndrome, rheumatism, vitamin deficiency, obesity, vascular diseases, infections, loss of appetite, dysmenorrhea, fever, atherosclerosis, detoxification, anemia, and diabetes [254]. Plants In dermatology, the oral use of Orchis maculata L. extract is prevalent in folk medicine for senile itching, skin tuberculosis, and other dermatoses accompanied by cachexia and chronic diseases of the respiratory and gastrointestinal tracts.…”
Section: Pastinaca Sativa L Seler Family-apiaceaementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the pharmacological effects of P. sativa on various bodily systems, including the central nervous, respiratory, gastrointestinal, hepatic, skin, cardiovascular, and genitourinary systems [252], as well as its potential in mitigating stroke, atherosclerosis, and other coronary heart diseases. Additionally, P. sativa has been shown to have positive effects on cholecystitis, constipation, anorexia, stomach pain, bladder atony, spastic enterocolitis, mild insomnia, nephritis, dysuria, renal colic, endocrine disorders such as menstrual syndrome, rheumatism, vitamin deficiency, obesity, vascular diseases, infections, loss of appetite, dysmenorrhea, fever, atherosclerosis, detoxification, anemia, and diabetes [254]. Plants In dermatology, the oral use of Orchis maculata L. extract is prevalent in folk medicine for senile itching, skin tuberculosis, and other dermatoses accompanied by cachexia and chronic diseases of the respiratory and gastrointestinal tracts.…”
Section: Pastinaca Sativa L Seler Family-apiaceaementioning
confidence: 99%
“…The root of parsnip is a rich source of numerous bioactive compounds, including coumarins, furanocoumarins, polyacetylenes, essential oils, terpenes, and flavonoids [ 252 ]. Additionally, parsnip root is rich in various minerals such as potassium, manganese, magnesium, phosphorus, zinc, and iron, as well as carotene, starch, pectin, vitamins, and sugars [ 254 ].…”
Section: Introductionmentioning
confidence: 99%
“…The root of parsnip is a rich source of numerous bioactive compounds, including coumarins, furanocoumarins, polyacetylenes, essential oils, terpenes, and flavonoids [103]. Additionally, parsnip root is a rich source of various minerals such as potassium, 7 of 42 manganese, magnesium, phosphorus, zinc, and iron, as well as carotene, starch, pectin, vitamins, and sugars [105].…”
Section: Pastinaca Sativa L Seler Family -Apiaceaementioning
confidence: 99%
“…) Numerous studies have demonstrated the pharmacological effects of P. sativa on various bodily systems, including the central nervous, respiratory, gastrointestinal, hepatic, skin, cardiovascular, and genitourinary systems [103], as well as its potential in mitigating stroke, atherosclerosis, and other coronary heart diseases. Additionally, P. sativa has been shown to have positive effects on cholecystitis, constipation, anorexia, stomach pain, bladder atony, spastic enterocolitis, mild insomnia, nephritis, dysuria, renal colic, endocrine disorders such as menstrual syndrome, rheumatism, vitamin deficiency, obesity, vascular diseases, infections, loss of appetite, dysmenorrhea, fever, atherosclerosis, detoxification, anemia, and diabetes [105]. Furthermore, furanocoumarins extracted from parsnips have the ability to dilate peripheral vessels and coronary vessels of the heart, eliminate spasms of the bronchi and smooth muscles of the abdominal cavity, and have a moderate sedative effect.…”
Section: Pastinaca Sativa L Seler Family -Apiaceaementioning
confidence: 99%